2011
DOI: 10.1007/978-3-642-20074-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Treatment in Adventure and Role-Playing Games: A Playground for Adaptation and Adaptivity

Abstract: Although there is pedagogical support for using computer adventure and role-playing games in order to learn a second language (L2), commercial games often lack the instructional qualities for making their language comprehensible for learners. In an interdisciplinary approach, this paper proposes a technique for adapting in-game text in order to teach L2 vocabulary, grounded in research on second language acquisition and adaptive learning systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Some researchers have indicated that the games provided an ideal language learning context (Rankin et al., 2006). In the adventure game, players may actively use the language to engage in the gaming content rather than passively listening to teachers’ content introductions or explanations (Cornillie et al., 2011). The players needed to use the language to take actions (e.g., talk to the NPCs) and explore many different possibilities in the story (e.g., ask questions to NPCs to find out solutions) in order to complete a series of missions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers have indicated that the games provided an ideal language learning context (Rankin et al., 2006). In the adventure game, players may actively use the language to engage in the gaming content rather than passively listening to teachers’ content introductions or explanations (Cornillie et al., 2011). The players needed to use the language to take actions (e.g., talk to the NPCs) and explore many different possibilities in the story (e.g., ask questions to NPCs to find out solutions) in order to complete a series of missions.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) have found that adventure games were more motivating and engaged students to explore in meaningful contexts compared with non-adventure games by meta-analyzing game-based vocabulary learning studies. Adventure video games have been widely recommended by many researchers (e.g., Baltra, 1990; Cornillie et al., 2011) and reviewed in some studies (Chen et al., 2016; Hung et al., 2018). One of the benefits of adventure games was that they were interactive in nature.…”
Section: Computer Games For Vocabulary Learningmentioning
confidence: 99%
See 3 more Smart Citations